1971
DOI: 10.1017/s0021859600064510
|View full text |Cite
|
Sign up to set email alerts
|

Plant population and shading studies in barley

Abstract: Two barley experiments are described in which a range of plant populations were shaded during different periods of development. Shading during the ear development period caused considerable reductions in grain yield, largely by reducing the number of grains per ear. Shading during the grain-filling period caused no reduction in grain yield. It is suggested that under conditions of these experiments there was probably a potential surplus of carbohydrate available for grain filling and that grain yield was large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 5 publications
3
20
0
Order By: Relevance
“…It is generally accepted that ear number per unit area and grain number per ear are determined at or before anthesis (Hesiop-Harrison, 1969; Kirby, 1973) implying that few fertile Glers die after anthesis and that most viable florets at anthesis set seed. The product of the above two factors, grain number per ucit are3, is sometimes claimed to be the major determinant of sink capacity and yield (Willey & Holliday, 1971 ;Gallagher, Biscoe & Scott, 1975). Gallagher et al (1975) suggest that variation in grain size is sufficiently small to be ignored.…”
mentioning
confidence: 99%
“…It is generally accepted that ear number per unit area and grain number per ear are determined at or before anthesis (Hesiop-Harrison, 1969; Kirby, 1973) implying that few fertile Glers die after anthesis and that most viable florets at anthesis set seed. The product of the above two factors, grain number per ucit are3, is sometimes claimed to be the major determinant of sink capacity and yield (Willey & Holliday, 1971 ;Gallagher, Biscoe & Scott, 1975). Gallagher et al (1975) suggest that variation in grain size is sufficiently small to be ignored.…”
mentioning
confidence: 99%
“…Such factors may include the post-anthesis mechanisms of number and size of endosperm cells, but possible pre-anthesis determination should also be considered. Thus grain weight as well as number of grains appears to be influenced by pre-anthesis variations in assimilate production achieved through light intensity (Willey & Holliday 1971a), leaf area (Williams & Hayes, 1977) or disease (Carver & Griffiths, 1981), although these effects could equally be due to effects on the availability of previously-stored assimilate for post-anthesis re-translocation. The suggestion that the flow of assimilate from the rachis phloem into the endosperm, rather than storage capacity per se, provides the restriction which is apparent within the ear (Jenner, 1976) has yet to receive support from other workers.…”
Section: Discussionmentioning
confidence: 99%
“…'Thinned early' (TE); Willey & Holliday (1971a) had shown that 50% shading of barley crops during the period prior to anthesis reduced ear size by about 2-5 grains per ear, so this treatment was devised to produce the converse effect, i.e. to increase the number of grains by increasing insolation during the same period.…”
Section: Manipulation Of Assimilate Supply In Field Plotsmentioning
confidence: 99%
“…For example, early leaves that later become the lower leaves of cereals may contribute effectively to plant establishment including tiller production and grain primordial number, but contribute nothing directly to grain fill. Many tillers later abort as the growth potential is matched to resources [30]. Thus, at any given time, leaves may have very different importance and this is reflected in their ability to express resistance to pathogen challenge.…”
Section: Physiological and Environmental Interactions With Symptom Exmentioning
confidence: 99%
“…Thus, at any given time, leaves may have very different importance and this is reflected in their ability to express resistance to pathogen challenge. Old leaves down-regulate defence mechanisms [30] and are thus vulnerable to pathogen attack or, more likely, saprophyte colonisation. In non-crop plants this may have few consequences, however for crops with greatly extended grain filling periods it could still have some detrimental effects.…”
Section: Physiological and Environmental Interactions With Symptom Exmentioning
confidence: 99%